ANALISIS PENYELESAIAN TINDAK LANJUT HASIL PEMERIKSAAN LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN NGANJUK - Andy Chandra Pramana (Bilancia : Jurnal Ilmiah Akuntansi, 2022)
ABSTRACTThe research aims to explain the mechanism for completing the follow-up results of the examination of thefinancial statements of the Nganjuk Regency Regional Government. The analysis used includes Planning,Organizing, Actuating, Controlling (POAC). The focus of this research is how the Nganjuk Regency RegionalGovernment as an auditee in completing the follow-up of the examination results. This research is qualitativeresearch with a case study approach. The informants in this study are the Head of the Nganjuk RegencyFinancial and Asset Management Agency, the Head of Accounting and Reporting, the Head of Reporting Subsectionand Technical Staff for Accounting and Reporting which can be said to be a representative of theNganjuk Regency Regional Government and most often communicates with the Financial Audit Board (BPK).The results of this study show that the completion rate of follow-up examination results in Nganjuk Regency hasnot been 100% resolved. The factors that become obstacles in the completion of the follow-up of the examinationresults are the absence of special policies that regulate the completion of follow-up examination results,coordination with regional device organizations (OPD) is not optimal, lack of commitment and motivation fromthe leadership.Keywords: follow-up; examination result; financial statements ABSTRAKPenelitian bertujuan menjelaskan mekanisme penyelesaian tindak lanjut hasil pemeriksaan laporan keuanganPemerintah Daerah Kabupaten Nganjuk. Analisis yang digunakan meliputi Planning, Organizing, Actuating,Controlling (POAC). Fokus penelitian ini adalah bagaimana Pemerintah Daerah Kabupaten Nganjuk sebagaiauditee dalam menyelesaikan tindak lanjut hasil pemeriksaan. Penelitian ini merupakan penelitian kualitatifdengan pendekatan studi kasus. Informan dalam penelitian ini adalah Kepala Badan Pengelola Keuangan danAset Daerah Kabupaten Nganjuk, Kepala Bidang Akuntansi dan Pelaporan, Kepala Sub-bagian Pelaporan danStaf Teknis Bidang Akuntansi dan Pelaporan yang mana dapat dikatakan sebagai representatif dari PemerintahDaerah Kabupaten Nganjuk dan paling sering berkomunikasi dengan Badan Pemeriksa Keuangan (BPK). Hasilpenelitian ini menunjukkan bahwa tingkat penyelesaian tindak lanjut hasil pemeriksaan di Kabupaten Nganjukbelum 100% terselesaikan, adapun faktor yang menjadi penghambat dalam terselesaikannya tindak lanjut hasilpemeriksaan adalah belum adanya kebijakan khusus yang mengatur penyelesaian tindak lanjut hasilpemeriksaan, koordinasi dengan Organisasi Perangkat Daerah (OPD) tidak maksimal, kurangnya komitmen danmotivasi dari pimpinan.Kata kunci: tindak lanjut; hasil pemeriksaan; laporan keuangan